An observational study of the reliability and concurrent validity of heart rate variability devices in athletes - Johansson, Hedvig; Adderley, Emily; Clarke, Seán; McIntyre, Patrick; Reilly, Garreth; Caulfield, Brian; Holden, Sinead (Frontiers in Physiology, 2026)
BackgroundHeart rate variability (HRV) is a non-invasive indicator of autonomic nervous system function and is increasingly used in athlete monitoring. While electrocardiography (ECG) is the gold standard for HRV measurement, its use is limited in field settings.ObjectiveTo evaluate the intra-session reliability and concurrent validity of a smartphone-based PPG app for HRV measurement in athletes, compared to a Polar H10 chest strap and ECG.MethodsThis observational study included 37 trained participants (17 female; mean age 21.95 ± 3.69 years). HRV was recorded concurrently via ECG, Polar H10 chest strap, and the CameraHRV smartphone app in two repeated trials on the same day. Data were processed using device-specific software. Intra-class correlation coefficients (ICC), coefficient of variation (CV%), mean absolute percentage error (MAPE), and Bland–Altman plots were used to assess reliability and agreement.ResultsAll three devices showed good-to-excellent intra-session reliability for RMSSD (ICC range 0.83–0.90) and pNN50 (ICC range 0.87–0.92). The Polar chest strap had the highest consistency and lowest error compared to ECG (RMSSD MAPE: 2.16%). The PPG app also demonstrated strong validity (RMSSD MAPE: 17.49%) but wider limits of agreement.ConclusionBoth the Polar chest strap and smartphone PPG app demonstrated acceptable reliability and validity for short-duration HRV assessment in athletes. While the chest strap outperformed the PPG app in precision, the PPG app may offers a practical, low-cost alternative for athlete monitoring.